Performance Analysis of Dimming Methods in Visible Light Communication Systems - Mehmet Sonmez; Süleyman Börekoğlu (Journal of Advanced Research in Natural and Applied Sciences)
The Visible Light Communication (VLC) has been taken very attentions from many researchers due to its efficiency substructure. In specially, the VLC systems provide both lighting and data transmission at the same time. This paper has investigated the performance analyses of modulation schemes which support the brightness control for Visible Light Communication. In this sense, it has been focused on performance differences between M-ary VPPM (M-ary Variable Pulse Position Modulation) scheme and VPAPM (Variable Pulse Amplitude Position Modulation) which was proposed to ensure the multilevel transmission for VPPM scheme. In particular, a performance comparison has been given for both techniques with respect to Bit Error Rate by considering the same bit length consisted in a symbol. The investigated M-ary VPPM is modified by generating the signals of two power levels. Moreover, a VPAPM based-transmission model has been proposed to assure the accurate dimming target values under condition of long runs of same bits (1 s or 0 s) that encode the signal amplitude. However, the proposed system has lower data rate when compare to traditional VPAPM. Moreover, a receiver scheme has been suggested to decode received VPAPM signals. The performance of VPAPM demodulator architecture has been observed in terms of BER versus transmission distance between receiver and transmitter.